Boom-Bust Cycle, Asymmetrical Fiscal Response and the Dutch Disease - Ismail, Kareem (IMF Working Papers; Working Paper ;, 2010)
We examine the behavior of expenditure policy during boom-bust in commodity price cycles, and its implication for real exchange rate movements. To do so, we introduce a Dutch disease model with downward rigidities in government spending to revenue shock. This model leads to a decoupling between real exchange rate and commodity price movement during busts. We test our model's theoretical predictions and underlying assumptions using panel data for 32 oil-producing countries over the period 1992 to 2009. Results are threefold. First, we find that change in current spending have a stronger impact on the change in real exchange rate compared to capital spending. Second, we find that current spending is downwardly sticky, but increases in boom time, and conversely for capital spending. Third, we find limited evidence that fiscal rules have helped reduce the degree of responsiveness of current spending during booms. In contrast, we find evidence that fiscal rules are associated with a significant reduction in capital expenditure during busts while responsiveness to boosts is more muted. This raises concerns about potential adverse consequences of this asymmetry on economic performance in oil-producing countries.